Implementation of the qanun no smoking area regulation at SMP Negeri 32 Takengon - Satria Budi; Donal Nababan; Frida Lina Tarigan; Kesaktian Manurung; Mido Ester J. Sitorus (Institute of Computer Science (IOCS), 2026)
Smoke-free areas are (SFA) an important policy in creating a healthy environment, especially in schools. This study aims to analyze the implementation of Takengon City Regulation No. 10 of 2013 on smoke-free areas at SMP Negeri 32 Takengon, identify the monitoring mechanisms applied, and examine the factors that hinder the effectiveness of the policy. This study uses a qualitative descriptive approach. The research was conducted at SMP Negeri 32 Takengon from January to June 2025. There were 10 informants in this study, consisting of 1 school principal, 1 homeroom teacher, 1 guidance counselor, 6 students, and 1 parent. The data collection techniques used in this study were in-depth interviews, observation, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was tested using source triangulation to ensure the accuracy of the research results. The results showed that the implementation of the Qanun KTR had a positive impact on the school environment. Supervision was carried out through routine patrols, the installation of no smoking signs, and periodic inspections. However, there are still obstacles such as the absence of Standard Operating Procedures (SOPs), inconsistency in the application of sanctions between students and staff, and a lack of involvement from parents and external parties in supervision. It is necessary to develop SOPs, apply fair sanctions, and increase cooperation with parents and relevant agencies to strengthen the effectiveness of the smoke-free zone policy.